Adherence to triage pain scoring at emergency department of Hospital Universiti Sains Malaysia - Zakarai, Norlaili (2016)
Introduction: The aim of this study was to determine the level of adherence to triage pain scoring documentation at ED HUSM and to determine the associated factors that influence the adherence to triage pain score, so that actions can be made later to improve emergency services on evaluating pain and providing immediate analgesia to the patients in the future. Methodology: This study was a cross sectional study of a six months period from July 2014 until December 2014. A total of 334 samples included in the study. Information obtained from triage paper of those adult patients presented in pain and staffs who fulfil the inclusion criteria were documented on data collection sheets. All data were analysed using descriptive analysis, simple logistic regression and multiple logistic regression. Results: Out of 334, only 94 (28.1%) sample showed adherence to documentation of pain score, while remaining 240 patients (71.9%) showed non adherence to triage pain score documentation. SN has about 4 times more likely compared to AMO to adhere to pain score documentation (95% CI : 2.11, 7.03. p-value = <0.001). When number of patient increase by 1, ED triage staffs have about 1 time less likely to be adhered to pain score documentation (95% CI : 0.96, 0.99. p-value = <0.001). When systolic BP of patient increase by 1mm/Hg, ED triage staffs have about 1 time less likely to be adhered to pain score documentation(95% CI : 0.976, 0.99. p-value = 0.004). Abdominal pain has 4 times more likely compared to trauma or limb pain, for ED triage staffs to adhere to pain score documentation (95% CI : 2.17, 8.44. p-value = <0.001). Back pain has 4 times more likely compared to trauma or limb pain, for ED triage staffs to adhere to pain documentation (95% CI : 1.43, 9.71). p-value = 0.007). Conclusion: There was poor adherence to triage pain score documentation at ED HUSM during the study period. Factors that influence the adherence to triage pain score documentation were position of staff, number of patients per shift, SBP, and sites of pain.